The Use of iMessage Tapbacks as Sequence-Closing Seconds - Leanna Rudin (Studies in Applied Linguistics & TESOL, 2025)
This study investigates iMessage Tapbacks as sequence-closing seconds, or minimal responses that fulfill conversational obligations in text-based group chats. Through conversation analysis of three group conversations, the analysis demonstrates how Tapbacks operate as efficient second pair-parts (2pps) in adjacency pairs: (1) likes acknowledge directives (e.g., agreeing to plans), (2) loves signal appreciation for commissives (e.g., offers), and (3) emphasize affiliates with tellings (e.g., complaints). Findings indicate that Tapbacks address interactional challenges by enabling acknowledgment without prolonging discussion, particularly in asynchronous, multi-topic chats. The study contributes to digital communication research by distinguishing Tapbacks from emojis and theorizing their role in replicating nonverbal cues (e.g., nods) while streamlining interaction. Limitations include a small, homogenous dataset; future research should examine demographic variation and contextual ambiguity in Tapback usage.